Mitos Bocah Sukerta dalam Masyarakat Jawa (Telaah Terhadap Serat Manikmaya) - Safii, Muhammad (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2019)
Serat Manikmaya is a manuscript of the collection Yogyakarta Sanabudaya Museum and is the work of the famous poet Kraton Kesunanan Surakarta Adiningrat, namely Raden Bagus Burhan or Raden Ngabehi Ranggawarsita III. In his work there are uniqueness to study, including: 1. Myth of children or bocah sukerta, 2. Birth of Batara Kala. The purpose of this study are: 1. to study the meanings contained in in the Serat Manikmayacript or manuscript collection number PB.. A 374, 2. Ranggawarsita?s motivationwrites Serat Manikmaya. The methodology used to method found in the science of philology, namely: 1. Inventory the manuscript, 2. Describing script. Inside the script of Serat Manikmaya has pasemon or symbol and meaning, the writer uses Roland Barter?s semiotic theory. The results of this study include: 1. Stories of sukertachildren who fall prey to Batara Kala, 2. How to ruwat children who are sukerta 3. Intellectual contributions to Hinduism and Islam, 4. History of Kraton Kasunanan Surakarta Adiningrat especially in pattern fields religious, 5. Ranggawarsita?s biography 6. Description of Serat Manikmaya script.Keywords: Serat Manikmaya, Sukerta, Ruwatan, Ranggawarsita